Tumors in Epilepsy - Nowell, Mark; Miserocchi, Anna; McEvoy, Andrew W. (Seminars in Neurology, 2015)
Primary brain tumors are common causes of focal epilepsy, accounting for 5% of new-onset seizures in adults and over 10% of lesional focal epilepsies. These epilepsies are often refractory to medical treatment, and high rates of seizure freedom can be achieved with gross total resections. However, the management strategy is not straightforward, and should be decided on a case-by-case basis in a multidisciplinary team, considering the natural history of the tumor, the likelihood of seizure freedom following surgical resection, the risks of surgery, and the impact of seizures on quality of life. In this review, the authors summarize the crucial factors that help to decide how to manage this challenging patient group.
Keywords: epilepsy; tumors; surgery